Leptospirosis manifested with severe pulmonary haemorrhagic syndrome successfully treated with venovenous extracorporeal membrane oxygenation - Chaikajornwat, Jukkaphop (BMJ Case Rep, 2020)
Leptospirosis, one of the most important of neglected tropical diseases, is a common zoonosis in the tropics. Recent reports have demonstrated that pulmonary haemorrhage is one of the fatal complications of severe leptospirosis. In this report, we present a case of leptospirosis manifested with severe pulmonary haemorrhagic syndrome successfully treated with venovenous extracorporeal membrane oxygenation (VV-ECMO). A 39-year-old man who lives in Bangkok presented with fever, severe myalgia and haemoptysis. With rapid progression of acute respiratory failure in 6 hours, he was intubated and a litre of fresh blood was suctioned. Chest x-ray showed diffuse alveolar infiltrates compatible with ARDS, then mechanical ventilator with lung protective strategy was used. Diagnosis of leptospirosis with diffuse alveolar haemorrhage was made. Refractory hypoxaemia was not responsive to positive end-expiratory pressure (PEEP); thus, VV-ECMO was initiated on the first day. Other treatments included plasmapheresis, intravenous pulse methylprednisolone and intravenous antibiotics. The outcome of treatment was successful, and this patient was discharged to home on day 14 after admission.